Effects of mental health training on capacity, willingness and engagement in peer‐to‐peer support in rural New South Wales. (8th July 2021) - Maddox, Sarah; Powell, Nicholas N.; Booth, Angela; Handley, Tonelle; Dalton, Hazel; Perkins, David
Abstract: Issue addressed: Rural Australians experience significant barriers in accessing mental health services, some of which may be overcome by increasing mental health literacy in rural communities. This paper evaluates Mental Health Support Skills (MHSS), short training courses developed by the Rural Adversity Mental Health Program (RAMHP). MHSS was designed to build the capacity of community members and gatekeepers to identify people with mental health concerns and link them to appropriate resources or services. Methods: Program data from April 2017 to March 2020 were analysed to assess the reach and outcomes of MHSS training. Training feedback was collected through a post‐training survey, completed directly after courses, and a follow‐up survey two months after training. An app used by RAMHP coordinators (the trainers) recorded the geographic and demographic reach of courses. Results: MHSS was provided to 10, 208 residents across rural New South Wales. Survey participation was 49% (n = 4, 985) for the post‐training survey and 6% (n = 571), for the follow‐up survey, two months post‐training. The training was well‐received and increased the mental health understanding and willingness to assist others of most respondents (91%‐95%). Follow‐up survey respondents applied learnings to assist others; 53% (n = 301) asked a total of 2, 252 people about their mental health in the two months following training. Those in clinical roles asked a median of 6 people about their mental health, compared to 3 for those in nonclinical roles. Most follow‐up survey respondents (59%, n = 339) reported doing more to look after their own mental health in the two months after training. Conclusion: These results are encouraging as they suggest that short‐form mental health training can be an effective tool to address poorer mental health outcomes for rural residents by improving the ability of participants to help themselves and the people around them. So what?: Serious consideration should be given to short mental health courses, such as MHSS, to increase literacy and connection to services, especially in rural areas.